Intrinsic motivations in health and fitness app engagement: A mediation model of entertainment - Thuy Dung Pham Thi; Nam Tien Duong (Digital Health)
Objective This study aims to investigate the intrinsic motivations driving continued usage of health and fitness apps, addressing a gap in the literature where user motivation has received limited attention. The study focuses on the role of entertainment as a mediator between intrinsic motivations and continuance intention, using the Uses and Gratifications Theory as a conceptual framework. Methods Data were collected through an online survey of 2869 health and fitness app users in Vietnam. Intrinsic motivations were categorized into challenge, curiosity, fantasy, and social interaction. Hypotheses were tested using SEM, and subgroup analyses were conducted to examine variations across demographic groups. Results The findings reveal that entertainment mediates the relationship between intrinsic motivations and continuance intention, with challenge and curiosity being the strongest predictors of sustained app usage. Challenge also demonstrated a direct effect on continuance intention, independent of entertainment. Demographic analysis indicated that males are primarily motivated by challenge and curiosity, while females and higher-income users are driven more by curiosity. Conclusion This study highlights the importance of intrinsic motivations in shaping user engagement with health and fitness apps. Practical implications include the need for app developers to design features that align with user motivations, such as gamified challenges, personalized content, and interactive elements. Future research should explore extrinsic motivations and validate the framework across other digital platforms to expand its applicability.